The Analysis of Topeng Sinok Dance in Brebes Regency - Sintho Rukmi, Dinar Ayu; -, Indriyanto (Harmonia: Journal of Arts Research and Education, 2015)
Topeng Sinok dance is the characteristic art of Brebes regency. This dance tells about the typical women in Brebes who are hard-working. Beauty, flexibility, and elegance do not reduce their love for nature and farming. This dance is a combination of Cirebon, Banyumas, and Surakarta style. The dance is basically aiming at showing that women from the border areas of Central and West Java are not spoiled, whiny, and lazy. Topeng Sinok dance is performed beautifully, elegant, and swift. This paper purposes to uncover the meaning behind Topeng Sinok dance movement. This study implements qualitative method that uses qualitative descriptive approach. The data collection process was conducted by using observation, documentation, and interview techniques. Further, the data were analysed by using dance data analysis by following the steps of (1) identifying and describing components; (2) understanding; (3) interpreting; and (4) evaluating. The data were then validated by using triangulation.